Visions of the state and society in the program documents of the Decabrists – a comparative analysis of Pavel Pestel’s “Russian Truth” and Nikita Muravyov’s “Constitutional Project” - Bizan, Zofia (Mundus Slavicus I, 2025)
The purpose of the article is a comparative analysis of program documents in two decabrist organizations – Nikita Muravyov’s “Constitutional Project” and Pavel Pestel’s “Russian Truth”. The texts are placed in historical, philosophical and biographical contexts. Comparative analysis consists of: contents of introductions, visions of the political system, the administrative division, organization of society, the approaches to the national question, and references to history and philosophy. The analysis was based on source texts and scientific studies.